2022
DOI: 10.1038/s41597-022-01796-3
|View full text |Cite
|
Sign up to set email alerts
|

Near-real-time daily estimates of fossil fuel CO2 emissions from major high-emission cities in China

Abstract: Cities in China are on the frontline of low-carbon transition which requires monitoring city-level emissions with low-latency to support timely climate actions. Most existing CO2 emission inventories lag reality by more than one year and only provide annual totals. To improve the timeliness and temporal resolution of city-level emission inventories, we present Carbon Monitor Cities-China (CMCC), a near-real-time dataset of daily CO2 emissions from fossil fuel and cement production for 48 major high-emission ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Current carbon emission databases (China Emission Accounts and Datasets, CEADs; Multi-resolution Emission Inventory, MEIC) and studies [5] have completed annual country/provincial sectoral carbon accounting, which usually uses the "bottom-up" approach to aggregate carbon emissions by sector and energy type in the region. In the pursuit of spatial accuracy, some studies have been conducted at the municipal level [22] and point-source carbon emissions [12]. In addition, existing emission inventories usually have a time horizon of years and a lag of more than two years, so the temporal accuracy of carbon emission measurements has been further extended to monthly [23], daily [24,25], and real time [26].…”
Section: Literature Review On Co 2 Monitoring Methodsmentioning
confidence: 99%
“…Current carbon emission databases (China Emission Accounts and Datasets, CEADs; Multi-resolution Emission Inventory, MEIC) and studies [5] have completed annual country/provincial sectoral carbon accounting, which usually uses the "bottom-up" approach to aggregate carbon emissions by sector and energy type in the region. In the pursuit of spatial accuracy, some studies have been conducted at the municipal level [22] and point-source carbon emissions [12]. In addition, existing emission inventories usually have a time horizon of years and a lag of more than two years, so the temporal accuracy of carbon emission measurements has been further extended to monthly [23], daily [24,25], and real time [26].…”
Section: Literature Review On Co 2 Monitoring Methodsmentioning
confidence: 99%
“…It should be pointed out that the seasonal variabilities in respiratory emission were not considered in this study, but there are obvious seasonal emission characteristics in fossil sources. For example, the near‐real‐time daily estimate of CO 2ff emissions for cities in China showed that there are obvious seasonal variations in CO 2ff emissions, which are about twice as high in winter as in early summer (Huo et al., 2022). Therefore, the estimated emission ratios of CO 2hr to CO 2ff were about 7% in winter, and usually reach the peak during spring and summer, with an average of about 15%.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The massive consumption of fossil energy has led to the excessive emission of greenhouse gases (GHGs) such as carbon dioxide (CO 2 ) and other hazardous gases, which has resulted in the increasingly severe greenhouse effect and other environmental problems. [5][6][7][8] Ecological crises such as global warming and glacier melting are daily affecting human life. Therefore, using reasonable technical means to convert CO 2 into chemicals with high attachment values is not only a way to achieve carbon emission reduction and carbon neutrality but also one of the effective ways to alleviate the energy crisis in the future.…”
Section: Introductionmentioning
confidence: 99%